Tryptophan Metabolites Along the Microbiota-Gut-Brain Axis: An Interkingdom Communication System Influencing the Gut in Health and Disease. (June 2020) - Bosi, Annalisa; Banfi, Davide; Bistoletti, Michela; Giaroni, Cristina; Baj, Andreina
The 'microbiota-gut-brain axis' plays a fundamental role in maintaining host homeostasis, and different immune, hormonal, and neuronal signals participate to this interkingdom communication system between eukaryota and prokaryota. The essential aminoacid tryptophan, as a precursor of several molecules acting at the interface between the host and the microbiota, is fundamental in the modulation of this bidirectional communication axis. In the gut, tryptophan undergoes 3 major metabolic pathways, the 5-HT, kynurenine, and AhR ligand pathways, which may be directly or indirectly controlled by the saprophytic flora. The importance of tryptophan metabolites in the modulation of the gastrointestinal tract is suggested by several preclinical and clinical studies; however, a thorough revision of the available literature has not been accomplished yet. Thus, this review attempts to cover the major aspects on the role of tryptophan metabolites in host-microbiota cross-talk underlaying regulation of gut functions in health conditions and during disease states, with particular attention to 2 major gastrointestinal diseases, such as irritable bowel syndrome (IBS) and inflammatory bowel disease (IBD), both characterized by psychiatric disorders. Research in this area opens the possibility to target tryptophan metabolism to ameliorate the knowledge on the pathogenesis of both diseases, as well as to discover new therapeutic strategies based either on conventional pharmacological approaches or on the use of pre- and probiotics to manipulate the microbial flora.